2020
DOI: 10.1016/j.redox.2020.101765
|View full text |Cite
|
Sign up to set email alerts
|

The necessity of NEDD8/Rub1 for vitality and its association with mitochondria-derived oxidative stress

Abstract: Access of molecular oxygen to the respiratory electron transport chain at the mitochondria costs in the generation of reactive oxygen-derived species (ROS). ROS induces progressive damage to macromolecules in all living cells, hence, rapid defense mechanisms to maintain cellular redox homeostasis are vital. NEDD8/Rub1 is a highly conserved ubiquitin-like modifier that has recently been identified as a key regulator of cellular redox homeostasis. In this review, I will present NEDD8/Rub1, its modification casca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 148 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…The electrons are then transferred along the ETC, while the released energy pumps proton from the matrix to the intermembrane space to form a proton gradient. When electrons are transferred to complex IV, the protons across the inner membrane back to the matrix where molecular oxygen, protons, and electrons react to produce H 2 O and the corresponding chemiosmotic power is captured by the membrane-spanning enzyme ATP synthase, thus catalyzing the addition of a phosphate to ADP (44)(45)(46). This ATP-forming process sounds perfect; however, the imperfection is that electrons may leak from the ETC and react with molecular oxygen without proton to generate superoxide anion, the prototype of ROS, which may cause damage to the cells (46,47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrons are then transferred along the ETC, while the released energy pumps proton from the matrix to the intermembrane space to form a proton gradient. When electrons are transferred to complex IV, the protons across the inner membrane back to the matrix where molecular oxygen, protons, and electrons react to produce H 2 O and the corresponding chemiosmotic power is captured by the membrane-spanning enzyme ATP synthase, thus catalyzing the addition of a phosphate to ADP (44)(45)(46). This ATP-forming process sounds perfect; however, the imperfection is that electrons may leak from the ETC and react with molecular oxygen without proton to generate superoxide anion, the prototype of ROS, which may cause damage to the cells (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…When electrons are transferred to complex IV, the protons across the inner membrane back to the matrix where molecular oxygen, protons, and electrons react to produce H 2 O and the corresponding chemiosmotic power is captured by the membrane-spanning enzyme ATP synthase, thus catalyzing the addition of a phosphate to ADP (44)(45)(46). This ATP-forming process sounds perfect; however, the imperfection is that electrons may leak from the ETC and react with molecular oxygen without proton to generate superoxide anion, the prototype of ROS, which may cause damage to the cells (46,47). It is originally believed that hypoxia-decreased O 2 supply to the mitochondria can reduce superoxide anion production, thus favoring a decrease in ROS content.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in mice, knockdown of CSN subunits is fatal in the early embryonic stage [ 33 ]. Although critical in multicellular organisms, the loss of CSN subunits in unicellular organisms does not always lead to inviability; examples are seen in various fungal species, including Aspergillus nidulans , Neurospora crassa, Schizosaccharomyces pombe, or Saccharomyces cerevisiae [ 34 , 35 ]. Cullin deneddylation is performed only when CSN5 resides in an intact CSN, attached to the CRL [ 16 , 17 , 18 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings showed that the levels of NEDD8 protein were increased in patients with hepatic steatosis compared to those in healthy controls. Oxidative stress, one of the key pathological features in the progression of NAFLD, could be related to the activation of neddylation [42][43][44]. Interestingly, our results showed that MLN4924 almost reversed the phenotypes of NAFLD induced by HFD, namely histological steatosis (Figure 4a), compared with mice fed with NCD.…”
Section: Discussionmentioning
confidence: 68%